Justice For The “Least”: Normative Reflections on The Protection of Children From Sexual Crimes - Pradata, Rizal; Fatimah, Siti Nur (Jurnal Indonesia Sosial Sains, 2025)
Sexual violence against children is an extraordinary crime. Sexual violence against children is a serious violation of human rights and social justice. Although it has been regulated in various laws and regulations, such as Law Number 35 of 2014 concerning Child Protection and its amendment through Law Number 17 of 2016, the practice of law enforcement against perpetrators of sexual crimes against children still leaves many problems, especially in terms of psychological protection and legal certainty for victims. Based on data from the Ministry of Women's Empowerment and Child Protection (Kemenpppa), throughout 2024, there were more than 11,771. This shows the urgency of more humane and victim-friendly handling. This article uses a normative approach to reflect on the extent to which the legal system in Indonesia is able to provide protection and justice for child victims of sexual violence. The main focus is directed at the analysis of applicable regulations, legal implementation, and structural challenges faced in realizing the principle of "the best interests of the child." Through this reflection, it is hoped that a collective awareness will emerge of the importance of building a legal system that is not only repressive towards perpetrators, but also restorative for victims—especially those who are most vulnerable: children.